A Late Woodland red ocher burial cache from Madison County, Ohio. (July 2015) - Nolan, Kevin C; Sciulli, Paul; Blatt, Samantha; Thompson, Christine K
An isolated human burial was discovered on a private property in Madison County, Ohio in the spring of 2009. The remains were recovered by the Ohio Bureau of Criminal Investigations and sent to The Ohio State University for analysis. We report the results of a generic descriptive analysis of the assemblage and remains. The individual was a robust young adult male, and the assemblage seemed typical of a terminal Archaic or Early Woodland period (1500–500 B.C.) deposit; however, a 14 C AMS analysis run on collagen from a rib of the burial yielded an estimated age of 1520–1370 BP (A.D. 430–580). The dating result indicates that there is much potential variability in the archaeology of central Ohio that is not well accounted for by current classification systems.